Correlation between the microstructure of carbon materials and their potassium ion storage performance. (March 2019) - Lin, Xiuyi; Huang, Jiaqiang; Zhang, Biao
Abstract: Alkali-metal ions storage in carbon materials is of great interests for developing high-performance anodes for batteries. While Li, Na ions storage has been extensively investigated, systematic studies on the correlation between K ions storage and carbon microstructure have rarely been conducted. The large radius of K ions leaves a legitimate question whether the charge storage sites for Li and Na ions are also active for K ions. Herein, electrospun carbon nanofibers are employed as model materials to explore the K-ion storage behaviors in carbon with representative microstructures. By combining in-situ characterization and theoretical calculations, three active sites have been unveiled, including (i) uptake of K-ion by defect sites; (ii) K ions adsorption on isolated graphene sheets in partially disordered carbon; (iii) K ions intercalation between graphene layers for carbon with a high degree of graphitization. A similar reversible capacity around 280 mAh/g is obtained for various carbon structures while their voltage profiles are highly disparate. Remarkably, it is found that non-graphitic carbon presents better rate capability and less temperature-dependence due to the faster ion diffusion. These findings offer new insights into the design of advanced carbon anode materials with tunable properties for K-ion batteries. Graphical abstract: